Bullying in School-Age Children - Veronica Veronica (Scientia Psychiatrica, 2022)
Bullying is a phenomenon in the form of negative actions against peers with the aim of hurting, done repeatedly, accompanied by physical or verbal aggression, relational disorders, which are hurting others by social manipulation, and malicious rumors. Bullying is a major public health problem should not be tolerated because it has a psychological impact on perpetrators and victims. The impact of bullying is increasingly widespread, it can even lead to suicide. Bullying in schools is the forerunner of violence in society. Emotional Mental Health Impacts caused by Bullying include symptoms of depression, anxiety, psychotic symptoms, ADHD symptoms, problems conduct, ASPD disorders, and suicide attempts. In addition, bullying also has an impact on substance abuse, crime, and delinquency. Seeing the magnitude of the impact, it is necessary tackle bullying in a holistic and comprehensive manner. The treatment consists of handling the whole school level, classroom level, and individual level, one of which is through CBT and parent training.